2020
DOI: 10.3390/en13184805
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Fly Ash Derived from Biomass Combustion in Fluidized Bed Boilers in Large Energy Power Plants as a Mineral Soil Amendment

Abstract: This research involved studying the physico-chemical parameters of fly ash derived from the combustion of 100% biomass in bubbling and circulating fluidized bed boilers of two large energy plants in Poland. Chemical composition revealed that ash contains substantial amounts of CaO (12.86–26.5%); K2O (6.2–8.25%); MgO (2.97–4.06%); P2O5 (2–4.63%); S (1.6–1.83%); and micronutrients such as Mn, Zn, Cu, and Co. The ash from the bubbling fluidized bed (BFB) was richer in potassium, phosphorus, CaO, and micronutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Samaras et al [56] demonstrated that ash and sewage sludge mixtures meet phytotoxicity and ecotoxicity standards when small amounts of fly ash are added to sewage sludge. However, in a study Jarosz-Krzemińska and Poluszyńska [58], biomass ash with desirable physicochemical properties added to soil exerted no toxic effects on seed germination or plant growth. In the current study, mixtures containing only CFA were most phytotoxic.…”
Section: Discussionmentioning
confidence: 94%
“…Samaras et al [56] demonstrated that ash and sewage sludge mixtures meet phytotoxicity and ecotoxicity standards when small amounts of fly ash are added to sewage sludge. However, in a study Jarosz-Krzemińska and Poluszyńska [58], biomass ash with desirable physicochemical properties added to soil exerted no toxic effects on seed germination or plant growth. In the current study, mixtures containing only CFA were most phytotoxic.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, the obtained results show that the studied fly ashes do not meet the requirements for utilization in the cement industry, as the unburned organic residuals are elevated [5,7]. Nevertheless, other applications, in which high content of organic matter either in an un-combustible or partially carbonized form is favorable, can be further investigated, such as implementation as soil-improving agencies, e.g., [30,31], or even in the environmental sector [32,33]. Additionally, the obtained results show that the studied fly ashes do not meet the requirements for utilization in the cement industry, as the unburned organic residuals are elevated [5,7].…”
Section: Organic Petrographical Featuesmentioning
confidence: 97%
“…Such action may be beneficial to avoid further land degradation and promote land restoration hence these issues are important in terms of Sustainable Development Goals (SDGs) [25,26]. The studies of biomass ashes in terms of fertilizer usefulness and environmental safety were conducted mainly for plant-origin biomass [27,28], and only limited studies for animal-origin biomass can be found in the literature. The majority of these studies relate to poultry litter ashes from combustion and gasification processes, while cow manure ash has been less studied.…”
Section: Introductionmentioning
confidence: 99%